Deformation Rate Analysis: How to determine in-situ stresses in unconventional gas reservoirs. (October 2021) - Fraser, Daniel; Gholami, Raoof; Sarmadivaleh, Mohammad
Abstract: Magnitude and direction of in-situ stresses are crucial inputs of any geomechanical analysis when it comes to the stability of structures under different downhole conditions. There have been many approaches proposed to determine these parameters on the laboratory or field scales, but many presumptions, complications and difficulties are often involved. Deformation Rate Analysis (DRA) is one of these approaches proposed to determine the magnitude of in-situ stresses based on the Kaiser effect in the applications concerning near surface conditions. In this paper attempts are made to show the application of the DRA in determination of in-situ stress for unconventional shale gas reservoirs. A case study from the Perth basin in Australia was considered to examine the accuracy of the results on the field scale. It was found that compliant shale samples may not be able to provide a good estimation of in-situ stresses, but the DRA appears to be an effective method of in-situ stress determination for unconventional shale gas reservoirs. The elapsed time between the sample extraction and testing also plays an important role during the laboratory measurements while the impact of the loading cycle on the strength of the samples should not be ignored.